2016
DOI: 10.1515/enr-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Progress in micro RNA focused research in endocrinology

Abstract: Micro RNAs (miRNAs) are small regulatory molecules of increasing biologists' interest. miRNAs, unlikely mRNA, do not encode proteins. It is a class of small double stranded RNA molecules that via their seed sequence interact with mRNA and inhibit its expression. It has been estimated that 30% of human gene expression is regulated by miRNAs. One miRNA usually targets several mRNAs and one mRNA can be regulated by several miRNAs. miRNA biogenesis is realized by key enzymes, Drosha and Dicer. miRNA/mRNA interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 137 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…Studies from several other laboratories have also demonstrated that miRNAs are associated with developmental programming of various organs (Zucchi et al 2013, Casas-Agustench et al 2015. The organs and tissues investigated include heart (Yan & Jiao 2016, Lock et al 2017), brain (Petri et al 2014) and several endocrine glands (pancreas, ovary, testes, hypothalamus and pituitary) (Kredo-Russo et al 2012, Voglova et al 2016. Of note, exposure to environmental toxins during human pregnancy affects miRNA expression in cord blood, which lead to increased disease susceptibility in offspring (Rager et al 2014, Gillet et al 2016).…”
Section: Mirna and Dohadmentioning
confidence: 99%
“…Studies from several other laboratories have also demonstrated that miRNAs are associated with developmental programming of various organs (Zucchi et al 2013, Casas-Agustench et al 2015. The organs and tissues investigated include heart (Yan & Jiao 2016, Lock et al 2017), brain (Petri et al 2014) and several endocrine glands (pancreas, ovary, testes, hypothalamus and pituitary) (Kredo-Russo et al 2012, Voglova et al 2016. Of note, exposure to environmental toxins during human pregnancy affects miRNA expression in cord blood, which lead to increased disease susceptibility in offspring (Rager et al 2014, Gillet et al 2016).…”
Section: Mirna and Dohadmentioning
confidence: 99%
“…Specific regulation is based on high complementarity between 2-8 nucleotides called seed sequence and 3´ untranslated region (3´UTR) of target genes. According to genome analysis of 3´UTRs, it has been estimated that more than 60 % of all human protein coding genes are regulated by miRNAs (Friedman et al 2009, Voglova et al 2016.…”
Section: Micrornasmentioning
confidence: 99%
“…This hypothesis is confirmed by treatment with DNA methyltransferases (DNMTs) and histone deacetylase inhibitors (HDACis) which renew the expression of multiple miRNAs in tumor cells [12,87]. The miRBase (http://www.mirbase.org/) records 1,881 miRNA precursors and 2,588 mature miRNAs [96,97], and certain miRNAs have been described in gastrointestinal stromal tumors [61,98]. Up-regulated miRNAs in GISTs are associated with the loss of 14q, tumor localization and risk level [61].…”
Section: "Oncomirs"mentioning
confidence: 93%